2022
DOI: 10.3390/healthcare10050948
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Use of the Internet Mediates the Association between Reduced Mentalization and Suicidal Ideation: A Cross-Sectional Study in Young Adults

Abstract: Suicide is a major public health problem, and it is urgent to investigate its underlying clinical and psychological concomitants. It has been suggested that low mentalization skills and problematic use of the internet (PUI) are factors that can play a role in suicidal behaviors. It is possible that poor mentalization skills contribute to leading to forms of PUI, which, in turn, can represent triggers for suicidal ideation (SI). We tested this hypothesis through a quantitative and cross-sectional study on a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…In fact, individuals with preoccupied or fearful attachment styles may excessively resort to social media platforms in order to alleviate anxiety in social interactions and fulfill their needs of relatedness and self-presentation [ 42 , 102 , 103 ]. In accordance with previous research [ 71 , 72 ], we also found a positive association between failures in mentalizing and PSMU. Accordingly, PSMU may represent an attempt to cope with unprocessed feelings by seeking refuge in an online environment perceived as more predictable and stable than offline interpersonal contexts [ 73 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, individuals with preoccupied or fearful attachment styles may excessively resort to social media platforms in order to alleviate anxiety in social interactions and fulfill their needs of relatedness and self-presentation [ 42 , 102 , 103 ]. In accordance with previous research [ 71 , 72 ], we also found a positive association between failures in mentalizing and PSMU. Accordingly, PSMU may represent an attempt to cope with unprocessed feelings by seeking refuge in an online environment perceived as more predictable and stable than offline interpersonal contexts [ 73 ].…”
Section: Discussionsupporting
confidence: 93%
“…Research suggests that failures in mentalizing are involved in addictive behaviors [ 67 , 68 , 69 , 70 ], including problematic online behaviors such as PSMU [ 71 , 72 , 73 ]. In fact, difficulties in identifying and regulating distressing feelings may increase the risk of resorting to substance use or engaging in dysfunctional behaviors as a means of seeking relief [ 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis also included a standard set of factors for each online behaviour model. However, several additional factors such as motivation, escapism tendencies [ 53 ], impulsivity [ 24 , 67 , 68 ], and compulsivity measures [ 1 ] should be introduced to better contextualise excessive online behaviours. Another set of variables that was not included in this analysis is exposure to COVID-19 (direct or indirect).…”
Section: Limitationsmentioning
confidence: 99%
“…Third, although the questionnaire was structured by inserting an attention control item similar to that in the study by Bersani et al ( 2022 ), it is necessary to consider various aspects regarding the completion of the survey: (i) it could be completed at any place, increasing the probability of making mistakes or paying little attention; (ii) it could be completed at any time, making it more likely here as well the possibility of providing responses that may have been influenced by different moods.…”
Section: Discussionmentioning
confidence: 99%
“…The following inclusion criteria were considered: (i) age over 18 years, (ii) ability to understand the Italian language (i.e., students from other countries temporarily in Italy through the ERASMUS program were excluded from the survey), (iii) be enrolled in a health profession degree program, (iv) to evaluate any random answer, based on another study (Bersani et al, 2022 ), one item of an attentional quality check (e.g., “Please score answer #5”) was proposed. The survey began with the acceptance of the informed consent.…”
Section: Methodsmentioning
confidence: 99%